APOE4 predicts amyloid-β in cortical brain biopsy but not idiopathic normal pressure hydrocephalus. Issue 11 (6th September 2012) - Pyykkö, Okko T; Helisalmi, Seppo; Koivisto, Anne M; Mölsä, Juhani A A; Rummukainen, Jaana; Nerg, Ossi; Alafuzoff, Irina; Savolainen, Sakari; Soininen, Hilkka; Jääskeläinen, Juha E; Rinne, Jaakko; Leinonen, Ville; et al.
Abstract : Objective: To investigate the association of apolipoprotein E ( APOE ) genotype, especially the APOE4 allele, to (1) idiopathic normal pressure hydrocephalus (iNPH) and (2) amyloid-β (Aβ) plaques in cortical brain biopsies of presumed NPH patients with and without a final clinical diagnosis of Alzheimer's disease (AD). Methods: 202 patients with presumed NPH were evaluated by intraventricular pressure monitoring and frontal cortical biopsy immunostained against Aβ (134 semiquantified by Aβ plaques/mm 2 ). The 202 patients and 687 cognitively healthy individuals were genotyped for APOE . The final clinical diagnoses in a median follow-up of 3.9 years were: 113 iNPH (94 shunt responsive, 16 shunt non-responsive, three not shunted); 36 AD (12 mixed iNPH + AD); 53 others. Results: The APOE genotypes distributed similarly in the 94 shunt responsive and 16 non-responsive iNPH patients and healthy controls. In multivariate analysis, the APOE4 allele correlated independently with Aβ plaques in the cortical biopsies (OR 8.7, 95% CI 3.6 to 20, p<0.001). The APOE4 allele in presumed NPH predicted later AD as follows: sensitivity 61%; specificity 77%; positive predictive value 37%; negative predictive value 90%. Conclusion: In presumed NPH patients, APOE4 associates independently with the presence of Aβ plaques in the frontal cortical biopsy. APOE4 is not a risk factor for iNPH and does not predict the response to shunt. Our data further support the view that the iNPH syndrome is a distinct dementing disease. Trial registration number: Kuopio NPH Registry (http://www.uef.fi/nph )